Gut Dysbiosis Has the Potential to Reduce the Sexual Attractiveness of Mouse Female - Yi, Xianfeng; Cha, Muha (Frontiers in Microbiology, 2022)
Increasing evidence has shown that gut microbiome has significant effects on mate preferences of insects; however, whether gut microbiota composition affects sexual attractiveness and mate preference in mammals remains largely unknown. Here, we showed that antibiotic treatment significantly restructured gut microbiota composition of both mouse males and females. Males, regardless of antibiotic treatment, exhibited higher propensity to interact with the control females than the antibiotic-treated females. The data clearly showed that gut microbiota dysbiosis reduced sexual attractiveness of females to males, implying that commensal gut microbiota influences female attractiveness to males. The reduced sexual attractiveness of the antibiotic-treated females may be beneficial to discriminating males by avoiding disorder of immunity and sociability in offspring that acquire maternal gut microbiota via vertical transmission. We suggest further microbiota work should be oriented to increase our understanding of the interactions between gut microbiota dysbiosis, sexual selection and mate choice of wild animals at the population level.